2006
DOI: 10.1007/s00425-006-0433-7
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids enhance the uptake of lead by wheat roots

Abstract: The uptake and bioavailability of lead (Pb) in soil-plant systems remain poorly understood. This study indicates that acetic and malic acids enhance the uptake of Pb by wheat (Triticum aestivum L.) roots under hydroponic conditions. The net concentration-dependent uptake influx of Pb in the presence and absence of organic acids was characterized by Michaelis-Menten type nonsaturating kinetic curves that could be resolved into linear and saturable components. Fitted maximum uptake rates (V max ) of the Michaeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…which is more easily absorbed or taken up by roots. The mechanism is very similar to the one verified for Cd (Wan et al, 2007). Only acetic acid application promoted an effective enhancement of Pb uptake, probably due to the low stability constant of complex and consequent higher facilitation for the plant uptake (Han et al, 2005).…”
Section: Effects Of Organic Acid Application In Root Uptakementioning
confidence: 53%
“…which is more easily absorbed or taken up by roots. The mechanism is very similar to the one verified for Cd (Wan et al, 2007). Only acetic acid application promoted an effective enhancement of Pb uptake, probably due to the low stability constant of complex and consequent higher facilitation for the plant uptake (Han et al, 2005).…”
Section: Effects Of Organic Acid Application In Root Uptakementioning
confidence: 53%
“…membrane transporters) and/or facilitated diffusion (ion channels). Most of the reports dealing with lead transport are related to terrestrial plants (Sunkar et al 2000;Wang et al 2007) and little is known about floating aquatic plants (Paganetto et al 2001). Olguín et al (2005) have suggested that in S. minima, Pb 2+ is accumulated intracellularly through the use of calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been understood that EDTA has a low biodegradability and is very persistent in the environment (Wasay et al 1998). Finally, acetic acid is very cheap and easily decomposed in the nature; the function of acetic acid in the heavy metal (Pb) accumulation by plant has been reported by hydroponics research (Wang et al 2007). Wang et al (2009) reported that acetic acid could promote Cu accumulation in wheat in contaminated soil.…”
Section: Introductionmentioning
confidence: 97%